2012
DOI: 10.1152/ajpheart.00493.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling mechanisms of arrhythmias in transgenic mouse heart overexpressing TNF-α

Abstract: Transgenic mice overexpressing tumor necrosis factor-α (TNF-α mice) possess many of the features of human heart failure, such as dilated cardiomyopathy, impaired Ca2+ handling, arrhythmias, and decreased survival. Although TNF-α mice have been studied extensively with a number of experimental methods, the mechanisms of heart failure are not completely understood. We created a mathematical model that reproduced experimentally observed changes in the action potential (AP) and Ca2+ handling of isolated TNF-α mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 70 publications
3
34
1
Order By: Relevance
“…Animals overexpressing TNF suffer from severe heart disease, including arrhythmia (26)(27)(28). This indicates that upregulation of TNF expression is closely associated with the dysfunction of cardiac myocytes (29,30). The results of the present study demonstrated that LPA is able to induce TNF-α release in cultured Jurkat T cells.…”
Section: Discussionsupporting
confidence: 55%
“…Animals overexpressing TNF suffer from severe heart disease, including arrhythmia (26)(27)(28). This indicates that upregulation of TNF expression is closely associated with the dysfunction of cardiac myocytes (29,30). The results of the present study demonstrated that LPA is able to induce TNF-α release in cultured Jurkat T cells.…”
Section: Discussionsupporting
confidence: 55%
“…This model is based on our previously published models for epicardial and endocardial cells [19], [20], [21], [22], which includes a comprehensive description of action potential, ionic currents, and Ca 2+ dynamics. For a description of myocyte contraction, we adopted Model 4 developed by Rice et al [15] by fitting experimental data on contraction for mice.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model for mouse ventricular myocyte contraction is a natural extension of our previously published models for action potential and Ca 2+ dynamics in mouse ventricular myocytes [19], with model improvements from [20], [21], [22] (Fig. 1A), developed for room temperature (298°K, or +25°C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations